Randomized comparison of interferon α and hydroxyurea with hydroxyurea monotherapy in chronic myeloid leukemia (CML-study II): prolongation of survival by the combination of interferon α and hydroxyurea - Hehlmann, Rüdiger; Berger, Ute; Pfirrmann, M.; Hochhaus, Andreas; Metzgeroth, Georgia; Maywald, O.; Hasford, J.; Reiter, Andreas; Hossfeld, D. K.; Kolb, H.-J.; Löffler, H.; Pralle, H.; et al. (Leukemia, 2003)
The optimum treatment conditions of interferon (IFN) α therapy in chronic myeloid leukemia (CML) are still controversial. To evaluate the role of hydroxyurea (HU) for the outcome of IFN therapy, we conducted a randomized trial to compare the combination of IFN and HU vs HU monotherapy (CML-study II). From February 1991 to December 1994, 376 patients with newly diagnosed CML in chronic phase were randomized. In all, 340 patients were Ph/BCR-ABL positive and evaluable. Randomization was unbalanced 1:2 in favor of the combination therapy, since study conditions were identical to the previous CML-study I and it had been planned in advance to add the HU patients of study I (n=194) to the HU control group. Therefore, a total of 534 patients were evaluable (226 patients with IFN/HU and 308 patients with HU). Analyses were according to intention-to-treat. Median observation time of nontransplanted living patients was 7.6 years (7.9 years for IFN/HU and 7.3 years for HU). The risk profile (new CML score) was available for 532 patients: 200 patients (38%) were low, 239 patients (45%) intermediate, and 93 patients (17%) high risk. Complete hematologic response rates were higher in IFN/HU-treated patients (59 vs 32%). Of 169 evaluable IFN/HU-treated patients (75%), 104 patients (62%) achieved a cytogenetic response that was complete in 12% (n=21), major in 14% (n=24), and at least minimal in 35% (n=59). Of the 534 patients, 105 (20%) underwent allogeneic stem cell transplantation in first chronic phase. In the low-risk group, 65 of 200 patients were transplanted (33%), 30 (13%) in the intermediate-risk group, and nine (10%) in the high-risk group. Duration of chronic phase was 55 months for IFN/HU and 41 months for HU (P<0.0001). Median survival was 64 months for IFN/HU and 53 months for HU-treated patients (P=0.0063). We conclude that IFN in combination with HU achieves a significant long-term survival advantage over HU monotherapy. In view of the data of CML-study I, these results suggest that IFN/HU is also superior to IFN alone. HU should be combined with IFN in IFN-based therapies and for comparisons with new therapies.